Global inflation: modern determinism and challenges for policy - Ye. N. Smirnov (Управление)
The article studies global inflation determinants, causing it in recent decades and at the present stage under the influence of cascading shocks in world economy and financial system.   The relevance of the problems summarized and analyzed in the article is explained by the significant risks of the inflation duration at the present stage, which is affected by an increasing number of shocks from demand, supply, and global financial system. In these conditions, even adaptive monetary policy may cease to be effective.   The purpose of the study is to assess the nature and extent of developed and developing countries’ economies vulnerability due to inflationary shocks and to identify the inflation fundamental determinants in crisis conditions on the basis of retrospective analysis.   Achievement of the goal implied the solution of such priority tasks as: global inflation dynamics factors identification considering the risks of stagflationary and recessionary trends in world economy; inflation new determinants identification in the context of changes in the scale and structure of the global financial market; assessment of monetary policy adjustment and adaptation mechanisms in the current inflationary environment; consideration of the current nature of supply and demand shocks and their impact on global inflation.   The current inflationary shock is unprecedented, and the study assesses it in its historical context and for its similarities and differences with significant inflation episodes observed in the post-war decades. The key factors of inflation at the present stage have been analyzed in their relationship with the monetary policy key trends.